Test of Cow Urine POC And Cocopeat on The Growth of Cocoa (Theobroma cacao L) Seedlings - Sulardi, Sulardi; Hakim, Tharmizi (Universitas Labuhanbatu, 2022)
Cocoa (Theobroma cacao L) is an annual plant that can bear fruit at the age of 4 years and if managed properly, it’s production can last more than 25 years. Seeding is a technique for multiplying plants by vegetative and generative methods. The purpose of this research is to determine the effect of application of cow urine POC and cocopeat on the growth of cocoa plant seeds and the effect of their interaction. This study used a factorial randomized block design (RAK) consisting of 2 treatment factors, namely the application of cow urine POC (S) consisting of 4 levels, namely S0 (0 ml/polybag), S1 (150 ml/polybag), S2 300 ml/polybag. ) and S3 (450 ml/polybag) and the application of cocopeat (C) consisted of 4 levels, namely C0 (0 g/polybag), C1 (100 g/plobag), C2 (200 g/polybag) and C3 (300 g/polybag).. Parameters observed were plant height (cm), number of leaves (strands), stem diameter (mm), wet weight (g), dry weight (g). The results showed that the application of cow urine POC had no significant effect on stem diameter, but had a significant effect on plant height, number of leaves and plant dry weight, and had a very significant effect on wet weight of cocoa seedlings. The application of cocopeat had no significant effect on plant height and stem diameter, but it had a very significant effect on the parameters of the number of leaves, plant wet weight and plant dry weight. The interaction between the application of cow urine POC and cocopeat had no significant effect on plant height, number of leaves, stem diameter, wet weight and dry weight of plants.